Cartesian and joint space teleoperation for nonholonomic steerable needles - Majewicz, A.; Okamura, A. M. (2013 World Haptics Conference (WHC 2013, 2013)
Robotically steered needles can improve clinical procedures by curving significantly within the body to attain targets and avoid obstacles. Needles that steer by tip asymmetry are nonholonomic systems, which are difficult to control manually (i.e. in joint space) due to under-actuation and unintuitive kinematic constraints. We propose a new teleoperation approach for nonholonomic systems (steerable needles in particular) that allows a user to command the desired position of a robot in Cartesian space and provides force feedback to represent kinematic constraints and the position error of the robot. We performed a user study with a virtual environment to evaluate the effectiveness of Cartesian space teleoperation in comparison to traditional joint space teleoperation, as well as the role of force feedback in Cartesian space teleoperation. Time-to-target and needle insertion length were significantly smaller for Cartesian space control than for joint space control, and when combined with force feedback, Cartesian space control resulted in significantly less targeting error than joint space control. Force feedback during Cartesian space control also reduced tracking error between the user and needle during insertion. Users rated Cartesian space control as easier overall; however, a few subjects felt they had less direct control of the needle.